Lychee Seed Fraction Inhibits Aβ(1-42)-Induced Neuroinflammation in BV-2 Cells via NF-κB Signaling Pathway - Zhao, Ya; Zeng, Yuan; Wu, Anguo; Yu, Chonglin; Tang, Yong; Wang, Xiuling; Xiong, Rui; Chen, Haixia; Wu, Jianming; Qin, Dalian (Frontiers in Pharmacology, 2018)
In our previous studies, an active fraction derived from Lycee seed, could inhibit β-amyloid induced apoptosis of PC12 cells and neurons. The primarily microglia cells are recognized as the brain's resident macrophages and thought to remodel of the brain by removing presumably redundant, apoptotic neurons. In the current study, we aimed to investigate the anti-neruoinflammation effect of Lycee seed fraction (LSF) in Aβ(1-42)-induced BV-2 cells and the underlying mechanism. The morphology results displayed that LSF could improve the status of Aβ(1-42)-induced BV-2 cells. The ELISA, real-time PCR and western blotting results showed that LSF could significantly reduce the release, mRNA level and protein expression of the pro-inflammatory mediators such as interleukin-1β (IL-1β), tumor necrosis factor alpha (TNF-α), cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) in Aβ(1-42)-induced BV-2 cells, which are down-regulated through suppressing the NF-κB signaling pathway. Furthermore, LSF could up-regulate Bcl-2 and down-regulate Bax, Caspase-3 and cleaved-PARP correspondingly. Taken together, our results firstly demonstrated that LSF could suppress the inflammatory response via inhibiting NF‐κB signaling pathway, and inhibit apoptosis in Aβ(1-42)-induced BV‐2 cells. Our findings further prove that LSF as a potential drug may be used for treating AD in the future.